2008
DOI: 10.11141/ia.24.5
|View full text |Cite
|
Sign up to set email alerts
|

Measuring women's influence on Roman military life: using GIS on published excavation reports from the German frontier

Abstract: 2This article outlines the approaches used in the Australian Research Council funded project, 'Engendering Roman Spaces', and summarises some of the results. The project investigates the distribution of artefacts and artefact assemblages and the presence, activities and status of women and children within Roman military forts. It uses data from published excavation reports of 1st-and 2nd-century AD Roman military sites on the German frontier. It includes excavation reports from throughout the 20th century, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…While precontact household studies in Polynesia typically investigate gender through the structured use of space within sleeping houses and cooking areas, historic studies have applied a broad use of artifact analyses to identify women's activities and social roles, similar to analyses worldwide (Allison 2006(Allison , 2008Beaudry-Corbett and McCafferty 2002;Keith 1998). In her analysis of the Te Puna Mission House in New Zealand, Middleton (2007Middleton ( , 2013 illustrated how artifact types found in the excavations signaled women's roles as teachers and reproducers of English society.…”
Section: Gender and Identitymentioning
confidence: 99%
“…While precontact household studies in Polynesia typically investigate gender through the structured use of space within sleeping houses and cooking areas, historic studies have applied a broad use of artifact analyses to identify women's activities and social roles, similar to analyses worldwide (Allison 2006(Allison , 2008Beaudry-Corbett and McCafferty 2002;Keith 1998). In her analysis of the Te Puna Mission House in New Zealand, Middleton (2007Middleton ( , 2013 illustrated how artifact types found in the excavations signaled women's roles as teachers and reproducers of English society.…”
Section: Gender and Identitymentioning
confidence: 99%
“…A number of the finds from Pons Tiluri are also military, including a pugio and scabbard from the Cetina River dating from the late 1 st century BC -mid 1 st AD, the approximate time Legio VII was stationed at Tilurium (Milošević 2009: 176-179). Nevertheless, non-combatants are found in forts across the Empire to differing degrees and their existence should not be disregarded a priori (van Driel-Murray 1997;Allison 2008;Greene 2020).…”
Section: The Legio VII 'Community Of the Soldier' And Its Articulatio...mentioning
confidence: 99%
“…Soldiers could find a partner, live with her and have offspring in a union not legally recognized under Roman law. Penelope Allison (2008) investigated the presence, activities and status of women and children in Roman military forts on the German frontier during the first and second centuries AD. She concluded that women played a greater role in military life in the early Roman Empire than has previously been acknowledged (see also Allison 2011Allison , 2013.…”
Section: A Migrant Population With a Skewed Sex Ratiomentioning
confidence: 99%